Phenotype-genotype correlations in X linked retinitis pigmentosa. Issue 9 (September 1992) - Kaplan, J; Pelet, A; Martin, C; Delrieu, O; Aymé, S; Bonneau, D; Briard, M L; Hanauer, A; Larget-Piet, L; Lefrançois, P
Abstract : Retinitis pigmentosa (RP) represents a group of clinically heterogeneous retinal degenerations in which all modes of inheritance have been described. We have previously found two different clinical profiles in X linked RP as a function of age and mode of onset. The first clinical form has very early onset with severe myopia. The second form starts later with night blindness with mild myopia or none. At least two genes have been identified in X linked forms, namely RP2 (linked to DXS7, DXS255, and DXS14) and RP3 (linked to DXS84 and OTC) on the short arm of the X chromosome. In order to contribute to phenotype-genotype correlations in X linked RP, we tested the hypothesis that the two clinical profiles could be accounted for by the two different gene loci. The present study provides evidence for linkage of the clinical form with early myopia as the onset symptom with the RP2 gene (pairwise linkage to DXS255: Z = 3.13 at theta = 0), while the clinical form with later night blindness as the onset symptom is linked to the RP3 gene (pairwise linkage to OTC: Z = 4.16 at theta = 0).